2019
DOI: 10.1002/ejoc.201900504
|View full text |Cite
|
Sign up to set email alerts
|

3,7‐Bis(N‐methyl‐N‐phenylamino)phenothiazinium Salt: Improved Synthesis and Aggregation Behavior in Solution

Abstract: In this paper, the optimization of the synthesis of 3,7‐bis(N‐methyl‐N‐phenylamino)phenothiazinium chloride with a detailed analysis of reaction parameters, i.e. solvent, temperature, amount of amine, as well as addition of a non‐nucleophilic base, is presented. Spectroscopic, electrochemical and computational data show that the presence of the two phenyl rings, directly bound on the PTZ+ core, inhibits the aggregation ability of the salt at concentrations up to 10–3 M. Furthermore, the introduction of an arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The structural diversity of these derivatives remains low despite their high potential. The main approaches to the introduction of arylamine fragments into the structure of phenothiazine are the Buchwald-Hartwig reaction [ 18 , 27 , 28 ] and the oxidation of phenothiazine to phenothiazin-5-ium cation followed by nucleophilic addition of aromatic amines ( Scheme 1 ) [ 17 , 21 , 25 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural diversity of these derivatives remains low despite their high potential. The main approaches to the introduction of arylamine fragments into the structure of phenothiazine are the Buchwald-Hartwig reaction [ 18 , 27 , 28 ] and the oxidation of phenothiazine to phenothiazin-5-ium cation followed by nucleophilic addition of aromatic amines ( Scheme 1 ) [ 17 , 21 , 25 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The distance between the planes of the heterocycles is 3.5 Å ( Figure 3 ). The geometry of the H-dimer of PTZ1 is similar to that of the H-dimer of MB [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that B3LYP and CAM-B3LYP better represent the absorption spectrum of 1H 2 in EtOH. Therefore, it can be assumed that WB97XD functional is suitable when a positive charge is delocalized over a π system, as previously observed [39,42]. Conversely, if the cation is located at the terminal position of a saturated alkyl side chain, and there is no interaction with the π-core, as in 1H 2 porphyrin, conventional functionals can be adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, spontaneous aggregation and limited solubility of the monomeric dyes affects the regularity of the polymer films obtained and the reproducibility of the modifier properties. Further improvement of the analytical and operational characteristics of electrochemical sensors calls for searching for new derivatives and their testing in the assembly of biosensors for drugs selection, in solar batteries, and in charge storage devices [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%